Engaging Hearts and Minds: Examining Narrative Transportation and Its Impact on Affective Engagement, Purchase Intention, and Online Brand Advocacy - Louati, Fatma; Ben Abdallah, Nada; Damak, Mouna (Tecno Scientifica Publishing, 2025)
In the context of increasingly competitive digital markets, it was important to understand how narrative transportation could increase purchase intention and produce online brand advocates. This study addressed the gap in prior research by examining the effect of narrative transportation on affective brand engagement. It also considered whether narrative transportation directly affected online brand advocacy and purchase intention in a virtual world. A quantitative approach was adopted, and a survey was distributed to Mercedes fans and users. The dataset contained a sample of 270 consumers, and the data were analysed using SPSS AMOS 23 to perform structural equation modeling. The results showed that narrative transportation had a positive effect on affective brand engagement in a virtual world. Similarly, the results indicated that narrative transportation strengthened online brand advocacy and purchase intention. By contrast, the findings revealed that emotional engagement did not directly impact online brand advocacy or purchase intention. These findings were regarded as valuable contributions to understanding how the transformation of storytelling into storydoing could engage consumers seeking captivating brand experiences. Future research could examine this study across other product categories to validate the generalizability of the findings, as well as incorporate additional variables to enrich the current model.